Managing new product development process: the Braskem case (Revista de Administração, 2007)
Nowadays, the search for competitiveness is strongly associated with the rapid introduction of new high value added goods and services in the market. In this context, the development of new products emerges as a core activity in the companies searching for long term sustainability. Aiming to contribute by providing evidences from Brazilian reality, this paper presents the study case of Braskem, a big Brazilian petrochemical company intensive on R&D activity . The study is qualitative-descriptive. The objective is to characterize the innovation process in the company. The indepth interview and a semi-structured questionnaire were used for collecting primary data and document analysis was used as secondary data. The results show that Braskem adopts a fast-follower technological strategy focusing continuous efforts in faster monitoring and following the competitors, identifying and assessing new markets-applications, technologies and knowledge sources. The company also uses technological platforms, pipelines and portfolio management for project's organization, selection and conduction. This approach recently adopted has modified significantly the innovation management. There are still important gaps to be surpassed, such as consolidating the continuous learning mechanisms. There are opportunities to be explored, such as increasing the access to R&D incentives available from government support programs and strengthen cooperation with universities and research institutes